Sternal osteomyelitis and scrofuloderma due to BCG vaccination (2003)
BCG vaccine has been used for nearly 100 years in the prevention of tuberculosis. The case of a 13 month-old girl vaccinated as a newborn with BCG is described as presenting a sternal mass with associated periostic erosion. The mass was resected, and histopathological examination revealed a chronic inflammatory reaction with caseous granulomas, and extension to bone and skin. PCR amplifications using specific primers for Mycobacterium tuberculosis on paraffin-embedded tissue were negative. BCG vaccination at birth, the histological appearance and the absence of M. tuberculosis DNA in the resected tissue indicated that osteomyelitis and scrofuloderma were a consequence of BCG. Osteomyelitis is a rarely occurring adverse effect of BCG vaccination, more commonly seen in immunosuppressed patients. In the patient described above, no symptoms of immunodeficiency were seen, however.